Only strict coronavirus regulations for vacationers affect passenger air traffic between Germany and Mallorca - Albert Banal-Esta\~nol; Wolfgang Grimme; Sven Maertens; Jo Seldeslachts; Christina Stadler (DIW Weekly Report, 2021)
Mallorca is the most popular foreign travel destination for German tourists, with almost five million flying to the Balearic island every year. However, the coronavirus pandemic brought passenger air traffic to a virtual standstill in March 2020. Flights to Mallorca resumed in June 2020, but the seat offerings were only between ten and 86 percent of the 2019 level depending on the week. This Weekly Report shows which coronavirus restrictions especially impacted air travel between Germany and Mallorca. For example, local restrictions such as curfews or outdoor mask requirements had little effect. Publicizing infection rates or publicly advising against flying also did little to influence travel behavior. Only strict travel restrictions such as entry bans and quarantine regulations had a significant impact on air travel. Thus, policymakers can only effectively manage travel by using such measures. At the same time, initial vaccination data shows that they significantly mitigate the effects of the strict travel restrictions.
Keywords: L93; H10; 330; Airline; COVID-19